2020
DOI: 10.1186/s40662-020-00204-4
|View full text |Cite
|
Sign up to set email alerts
|

Visual quality of juvenile myopes wearing multifocal soft contact lenses

Abstract: Background: It is unclear whether multifocal soft contact lenses (MFSCLs) affect visual quality when they are used for myopia control in juvenile myopes. The aim of this study was, therefore, to investigate the effect of MFSCLs on visual quality among juvenile myopia subjects. Methods: In a prospective, intervention study, thirty-three juvenile myopes were enrolled. Visual perception was assessed by a quality of vision (QoV) questionnaire with spectacles at baseline and after 1 month of MFSCL wear. At the one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
(51 reference statements)
1
13
0
Order By: Relevance
“…However, there is evidence that multifocal contact lenses wearers experience neuroadaptive adaptation through recruitment of visual attentional and procedural learning networks 41 . Indeed, previous studies reported an improvement in some visual parameters after periods of weeks or months 23,25 . Therefore, it is plausible that the variables measured here could improve after an adaptation period to this specific optical design.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, there is evidence that multifocal contact lenses wearers experience neuroadaptive adaptation through recruitment of visual attentional and procedural learning networks 41 . Indeed, previous studies reported an improvement in some visual parameters after periods of weeks or months 23,25 . Therefore, it is plausible that the variables measured here could improve after an adaptation period to this specific optical design.…”
Section: Discussionmentioning
confidence: 77%
“…For example, wearing multifocal soft contact lenses has been associated with an increased accommodative lag, which may lead to reduced image quality during near work 20–22 . Also, contrast sensitivity, light disturbance, higher order aberrations and visual comfort scores have been shown to be negatively affected by multifocal soft contact lenses used for slowing myopia progression, although no changes in visual acuity and stereopsis have been observed 16,17,23–26 …”
Section: Introductionmentioning
confidence: 99%
“…A trend to an increase in the perception of photic phenomena with the CL wear was observed but in most cases occasionally and inducing mild bothersomeness. Kang et al [42] and Huang et al [43] used a validated questionnaire of quality of vision to analyze the impact of off-label multifocal CL fitting for myopia control, reporting the presence of a certain level of blurred vision, visual fluctuation, focus difficulty and photic symptoms. Specifically, Huang et al [43] reported a decrease in these photic symptoms after one month of CL use, except for halos.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al [42] and Huang et al [43] used a validated questionnaire of quality of vision to analyze the impact of off-label multifocal CL fitting for myopia control, reporting the presence of a certain level of blurred vision, visual fluctuation, focus difficulty and photic symptoms. Specifically, Huang et al [43] reported a decrease in these photic symptoms after one month of CL use, except for halos. Our study showed a low incidence of glare and halos before and after CL wear, with no patient reporting the perception of moderate or severe glare or halos.…”
Section: Discussionmentioning
confidence: 99%
“…For the MFCL group, a daily disposable soft contact lens (BioThin, Bio Optic Inc., Taiwan, China) made of ocufilcon D [DK: 19 × 10 –11 (cm 2 /s) (mL O 2 /mL ∗ mmHg)] with a diameter of 14.2 mm and a base curve of 8.6 mm was used. The lenses were designed to have the spherical distance power at the central treatment zone of 0–3 mm diameter and a myopic defocus zone of 3–6 mm diameter ( Huang et al, 2020 ). Subjects were asked to wear the MFCL for at least 5 days/week, 8 h/day.…”
Section: Methodsmentioning
confidence: 99%